Metabolic characterization of the new benzimidazole synthetic opioids - nitazenes - Jadhav, Gajanan R.; Fasinu, Pius S. (Frontiers in Pharmacology, 2024)
The recent re-emergence and the increasing popularity of nitazenes, a group of new synthetic opioids (NSO) that belong to the benzimidazole chemical class, has raised public health concerns. As a class of potential opioid analgesic agents whose development was discontinued in the 1960s due to their high potential for abuse, very little is known about their metabolism and physiologic disposition. In the current study, three nitazenes–butonitazene, isotonitazene and protonitaze were incubated in human liver microsomes (HLM), human S9 (HS9) fractions and recombinant cytochrome P450 enzymes. All three nitazenes were rapidly metabolized in both HLM and HS9 with over 95% depletion within 60 min. In HLM, butonitazene, isotonitazene and protonitazene had in vitro intrinsic clearance (CLint) (µL/min/mg protein) values of 309, 221 and 216 respectively compared to 150 of verapamil, the positive control. In HS9, CLint values were 217, 139, and 150 for butonitazene, isotonitazene and protonitazene respectively compared to only 35 for testosterone, the control probe substrate. Putative metabolite identified from this study include products of hydroxylation, desethylation, dealkylation, desethylation followed by dealkylation, and desethylation followed by hydroxylation. The metabolic phenotyping showed CYP2D6, CYP2B6 and CYP2C8 and the major hepatic enzymes responsible for the metabolism of nitazenes. Within 30 min of incubation, CYP2D6 depleted butonitazene (99%), isotonitazene (72%) and butonitazene (100%) significantly. The rapid metabolism of nitazenes may be an important factor in accurate and timely detections and quantitation of the unchanged drugs in human matrices following intoxication or in forensic analysis. The involvement of multiple polymorphic CYPs in their metabolism may play important roles in the susceptibility to intoxication and/or addiction, depending on the activity of the metabolites.